If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -37 = -67 Reorder the terms: -37 + y = -67 Solving -37 + y = -67 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '37' to each side of the equation. -37 + 37 + y = -67 + 37 Combine like terms: -37 + 37 = 0 0 + y = -67 + 37 y = -67 + 37 Combine like terms: -67 + 37 = -30 y = -30 Simplifying y = -30
| -21=n-10 | | 2(2x+5)=40 | | 3(x-5)=2(x+1)+x | | 5+9x=-13 | | -5.7-44.2=-8.3v | | -7y+3=8y+1 | | 3(7x+20Y)7(-3x+6y)= | | 4x+8-3x-10=-33 | | -6-2x-1=4x+8-6x-3 | | 2(n+5)=11 | | 7=-11+3(6+5) | | 2(n+5)=111 | | -5r-r=5r-8 | | 3x+5x+4x-2=10 | | -10x+8-6x=-2-17x+9 | | 5.4x+8.6=3.4x-16 | | (10+2x)(20+2x)=336 | | 7x+6=3x+2 | | 2x-16y=7 | | 6(6g-2)+8(1+5g)=2g | | 6n-32=3n+7 | | 2x^2-4x=1.33333 | | 7t-6=330 | | (7+u)(5u-6)=0 | | 7x+8x+2x=12 | | -69=6(-3n-2)-(-5n-8) | | 19=x-32 | | A(-8)= | | 2y=x+13 | | 1+2p=16+7p | | 8x+15=5x+6 | | 9-x-4=45 |